2021
DOI: 10.1097/md.0000000000027990
|View full text |Cite
|
Sign up to set email alerts
|

Spinal fusion with motor evoked potential monitoring using remimazolam in Alström syndrome

Abstract: Rationale: Alström syndrome is a rare genetic disorder characterized by obesity, diabetes mellitus, cardiomyopathy, and liver dysfunction. Further, scoliosis, a common symptom of Alström syndrome, often requires surgical intervention for functional impairments. Motor evoked potential (MEP) monitoring and other electrophysiological tests are essential when performing surgery for functional scoliosis. However, there are few reports on how to maintain general anesthesia in Alström syndrome. Here, we describe a pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 9 publications
0
6
1
Order By: Relevance
“…The EEG effects of benzodiazepines are predominantly a monotonic beta activation, especially in frontal areas, and these effects map to higher EEG-derived indices to estimate the anesthesia depth [ 23 ]. In contrast to the current pediatric case, previous tc-MEP reports of young and elderly patients showed that relatively higher remimazolam infusion rates were required for successful MEP recording [ 6 , 7 ]. In neurosurgery, stimulating intensities should be minimized to the least possible extent to circumvent false-positive signals that result from the stimuli reaching the skull base [ 16 ]; this is the most significant difference from tc-MEP, which is frequently used in spine surgery.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…The EEG effects of benzodiazepines are predominantly a monotonic beta activation, especially in frontal areas, and these effects map to higher EEG-derived indices to estimate the anesthesia depth [ 23 ]. In contrast to the current pediatric case, previous tc-MEP reports of young and elderly patients showed that relatively higher remimazolam infusion rates were required for successful MEP recording [ 6 , 7 ]. In neurosurgery, stimulating intensities should be minimized to the least possible extent to circumvent false-positive signals that result from the stimuli reaching the skull base [ 16 ]; this is the most significant difference from tc-MEP, which is frequently used in spine surgery.…”
Section: Discussioncontrasting
confidence: 76%
“…Although no connection between propofol allergy and egg, soy, or peanut allergies were found in adults [ 3 ], it is still unclear whether propofol administration is safe in children allergic to certain foodstuffs [ 4 ]. Remimazolam, a short-acting benzodiazepine characterized by metabolism independent of organ function [ 5 ], was proposed as an alternative to propofol for spine surgeries in young and elderly patients who require intraoperative transcranial MEP (tc-MEP) recordings [ 6 , 7 ]. This study presents a pediatric case with egg hypersensitivity whose direct cortical MEP (dc-MEP) was successfully recorded under remimazolam anesthesia, instead of propofol.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that varying the administration rate of remimazolam from 0.5 mg/kg/h to 1.0 mg/kg/h has no effect on the MEP amplitude. 28 In addition, Kamata et al 29 showed that remimazolam could be used as an alternative sedative agent to propofol for MEP monitoring in neurosurgery, even for immature toddlers with neurodevelopment. Inhalation anaesthetics or a prolonged infusion of propofol will reduce the capacity for fatty acid utilization and mitochondrial activity, and thus increase the risk of rhabdomyolysis.…”
Section: Current Status Of Applications Of Remimazolammentioning
confidence: 99%
“…In another case report, a patient with Alstrom syndrome, a rare genetic disorder characterized by dilated cardiomyopathy, liver dysfunction, and scoliosis, underwent posterior spinal fusion and successful motor evoked potential monitoring with remimazolam 0.5 mg/kg/h for maintenance of general anesthesia. 27 A separate case report by Kondo et al 28 reported 2 patients undergoing spine surgery with general anesthesia maintained with remimazolam infusions. The effects on motor evoked potential waveforms in both patients were compared at different points, including baseline recordings, during laminoplasty, at the end of the procedure, and at escalating remimazolam infusions rates (0.5 up to 1.5 mg/kg/ h).…”
Section: Effects Of Remimazolam On Neuromonitoring: Electroencephalog...mentioning
confidence: 99%
“…In another case report, a patient with Alstrom syndrome, a rare genetic disorder characterized by dilated cardiomyopathy, liver dysfunction, and scoliosis, underwent posterior spinal fusion and successful motor evoked potential monitoring with remimazolam 0.5 mg/kg/h for maintenance of general anesthesia 27 . A separate case report by Kondo et al 28 reported 2 patients undergoing spine surgery with general anesthesia maintained with remimazolam infusions.…”
Section: Remimazolam Utilization During Neurosurgical Proceduresmentioning
confidence: 99%